2003
DOI: 10.3102/00346543073002231
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Career and Technical Education and Comprehensive School Reform: Implications for Research and Practice

Abstract: In the 1990s, federal legislation authorizing funding for secondary vocational education, increasingly called career and technical education (CTE), began to mandate accountability requirements such as improved academic achievement. These requirements have necessitated a search for ways to integrate CTE into broader school reforms that have improved student achievement as their goal. This review examines research on the effects of CTE reform efforts in general and on efforts to meld CTE with comprehensive secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 35 publications
2
72
0
2
Order By: Relevance
“…These findings are consistent with previous research suggesting that student career exploration can have positive effects on school engagement (Castellano et al, 2003;Kenny et al, 2006). The data also support the theoretical propositions of possible-selves theory (Markus & Nurius, 1986), which proposes that students will attend to their learning and view school as having more value when class content is provided in the context of information that the student values or considers relevant for future benefits and choices.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are consistent with previous research suggesting that student career exploration can have positive effects on school engagement (Castellano et al, 2003;Kenny et al, 2006). The data also support the theoretical propositions of possible-selves theory (Markus & Nurius, 1986), which proposes that students will attend to their learning and view school as having more value when class content is provided in the context of information that the student values or considers relevant for future benefits and choices.…”
Section: Discussionsupporting
confidence: 91%
“…Studies of school-to-work programs offered in high schools have consistently found that students in these programs exhibit higher psychosocial school engagement and lower rates of dropout than students not participating in career exploration (Castellano, Stringfield, & Stone, 2003;Plank, 2001). In a longitudinal study of low-income ninth-grade students, researchers reported that students with higher levels of career planning sustained higher levels of school valuing and feelings of belonging to their school (Kenny, Blustein, Hasse, Jackson, & Perry, 2006).…”
Section: Role Of Career Relevance and Instructionmentioning
confidence: 97%
“…The idea that workplace education fulfils unmet industry needs is implicit in the context of competency-based standards endorsed by government (Tight 1998;Blackwell et al 2001), or accountability requirements in career and technical education set by professional associations (Hargraves 2000;Castellano and Stringfield 2003). This was reflected in a pair of government reports published in the United Kingdom, known as the Dearing Report and the Fryer Report, each of which supported more workplace-centric education (Tight 1998;Blackwell et al 2001).…”
Section: The Problem: Workplace Education and Industrymentioning
confidence: 96%
“…Department of Education, 2000). Over the past 15 to 20 years, evidence linking indicators of academic success (e.g., grades, school attendance) and indicators of socioeconomic success (e.g., annual income, college enrolment) with indicators of career development (e.g., career exploration, career self-efficacy) has grown at a modest level (e.g., Castellano, Stringfield, & Stone, 2003;Fouad, 1995;Gysbers & Henderson, 2000;Lapan, Gysbers, & Petroski, 2001). Yet, these programs still do not represent mainstream approaches to school dropout prevention in the U.S. (Prevatt & Kelly, 2003).…”
Section: A Social Action Approach To Efficacy Researchmentioning
confidence: 98%